Safe Carrying of Heavy Infants Together With Hair Properties Explain Human Evolution - do Amaral, Lia Queiroz (Frontiers in Psychology, 2022)
As a physicist, my scientific career was interrupted by maternity, and afterwards retaken, with a parallel independent personal perspective on human evolution. My previous published contributions are reanalyzed as Hypothesis & Theory. The focus is on safe infant carrying in primates, sexual selection among Hominoidea, fur reduction in hominins, and tensile properties of hominoid hairs, justifying the necessary change to bipedal locomotion from the overwhelming selective pressure of infant survival. The Discussion starts with analysis of existing bias against acceptance of these new ideas, first with rational arguments on bias existing between Exact Sciences and Biological Sciences. A reanalysis of data on elasticity of hominoid hairs is made, based on published differences between statistical analysis of measurements in exact and inexact sciences. A table constructed from the original data on hair elasticity allows a simplified discussion, based on statistics used in Physics in the study of “known samples”, adding extra information to the available data. Published data on hair density in primates and mammals allow the conclusion that hair elastic properties might have evolved correlated to the pressure of safe carrying of heavy infants, with an upper limit of 1 kgf/cm2 for safe infant clinging to primate mother’s hair. The Discussion enters then on the main ideological bias, related to the resistance in the academy to the idea that bipedalism could be connected to a “female problem”, that means, that it was not a “male acquisition”. Tripedal walk, occurring naturally among African Apes carrying their newborns, unable to support themselves by ventral clinging, is the natural candidate leading to evolution of bipedal locomotion. Tripedal walk as an intermediate stage to bipedalism was in fact theoretically proposed, but ignoring its role in primate transportation by ape mothers. The Discussion proceeds to a proposal of phylogenetic evolution of Hominoids, the usual focus on the males changes to the role of females with infants, allowing an integrated view on Hominin evolution, with fur reduction and thermoregulation of the naked skin, with subcutaneous insulating fat layer. The model for earliest hominin social structures is based on huddle formation and hormonally defined rites of passage.